2020
DOI: 10.1021/acs.iecr.9b06997
|View full text |Cite
|
Sign up to set email alerts
|

Pd Supported on Alumina Using CePO4 as an Additive: Phosphorus-Resistant Catalyst for Emission Control in Vehicles Fueled by Natural Gas

Abstract: This work reports a novel strategy to improve phosphorus resistance of a model Pd catalyst on alumina using CePO4 as an additive, and the mechanism of phosphorus poisoning over the catalyst for methane removal under operational conditions was systematically investigated. The results demonstrated that phosphorus poisoning at 800 °C caused both harsh physical and chemical modifications in the Pd catalyst without the CePO4 additive; that is, the conversion of support aluminum oxide into a multilayer cristobalite-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…While when the reaction temperature is above 460 °C, Pd/CZA suffers from oxygen poisoning and shows signs of deactivation. On the contrary, since P can reinforce the active metal particles anchored on the composite support and prevent the loss of active components, , the ability of Pd/CZPA to continuously catalyze the conversion of methane is still maintained even at high temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…While when the reaction temperature is above 460 °C, Pd/CZA suffers from oxygen poisoning and shows signs of deactivation. On the contrary, since P can reinforce the active metal particles anchored on the composite support and prevent the loss of active components, , the ability of Pd/CZPA to continuously catalyze the conversion of methane is still maintained even at high temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…H 2 pre-treatment was performed before the in situ CO-DRIFTS test to reduce the Pd cations into a metallic state, which enhances the adsorption capacity of probe molecules (CO) and increases the signal intensity . This is because cationic Pd sites exhibit weaker interactions with CO molecules than metallic Pd sites. As shown in Figure a, only two bands located at 2112 and 2172 cm –1 for gaseous CO were observed over Pd/S-1, which is due to CO adsorption on large Pd particles without confinement. In contrast, clear CO adsorption bands were observed at 2090 and 1950 cm –1 over the encapsulated catalysts (i.e., Pd@S-1 and PdCe 0.4 @S-1) and can be assigned to the linear and bridging stretching vibrations of CO adsorption on Pd 0 sites, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…[192][193][194] Chen et al reported a novel Pd/alumina catalyst with CePO 4 modification, which shows enhanced performance in operational conditions but also excellent performance after phosphorous poisoning. 195 As for the unmodified alumina support, the phosphorus poisoning caused the generated cristobalite-type alumina phosphate to block the Pd active sites, dramatically decreasing performance. However, as for the modified catalyst, CePO 4 acting as a barrier layer can effectively suppress the formation of the inactive aluminum phosphate(as shown in Fig.…”
Section: Methane Combustionmentioning
confidence: 99%